ARTIFICIAL INTELLIGENCE IN POLITICS: CONTESTING POWER IN HUMAN AND NONHUMAN RELATIONS IN THE DIGITAL ERA - Caroline Paskarina (Jurnal Wacana Politik, 2024)
The discourse on technology and politics is still marked by two competing narratives: utopian and dystopian. The two narratives contest each other regarding who will be more powerful in the digital era, whether humans or technology. However, beyond this dichotomous debate, artificial intelligence has become inevitable and creates new power practices that cannot be adequately analyzed from these two extreme poles. This article discusses the nature of power in the contesting discourse on the creation of artificial intelligence and the implications of using artificial intelligence in politics. The literature study method is used to identify narratives that shape discourses about power at the intersection of technology and politics that develop in debates about the implication of artificial intelligence toward relations in two aspects of relations, human to non-human and human to human, as implicated in the utilization of AI. Analysis of the narrative behind the discourse on artificial intelligence is expected to reveal truth claims that legitimize the nature of power that appears in the digital era.